UPAYA PENINGKATAN KEMAMPUAN MOTORIK KASAR ANAK DOWN SYNDROME DENGAN OLAHRAGA BOLA KAKI DI GOLDEN KIDS - Sinto Robindo; Melda Rumia Rosmeri Simorangkir (Program Studi Bimbingan dan Konseling, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
ABSTRACT All aspects of development are very important in a person's life where the development of cognition, affection and psychomotor is well developed in accordance with its development, these three aspects can be said to be good and successful if the three aspects develop well. Like wise with the psychomotor aspect where between gross motor and fine motor are also balanced. Motoric is the development of coordinated body movement control between nerves, brain, and spinal cord (spinal cord or spinal cord). Child's gross motorization can be optimized by improving his motor movement coordination skills through physical activity in the form of coordination of body movements. Like throwing, catching, kicking, running, melopat, and maintaining balance. The condition of a Down Syndrome child who experiences weakness in the ability to think will affect in all aspects of his life. Down syndrome children have problems in cognitive abilities, effective and self-care abilities. This results in them needing special education. Basically, the educational goals that children with Down Syndrome want to achieve are not different from those of education in general. Because Down Syndrome children themselves are born in the midst of society. Keywords: football sports, gross motoric, down syndrome